A preliminary analysis of the effect of individual differences on cognitive performance in young companion dogs - Jordan G. Smith; Sarah Krichbaum; Lane Montgomery; Emma Cox; Jeffrey S. Katz (Animal Cognition)
Abstract Many factors influence cognitive performance in dogs, including breed, temperament, rearing history, and training. Studies in working dog populations have demonstrated age-related improvements in cognitive task performance across the first years of development. However, the effect of certain factors, such as age, sex, and temperament, on cognitive performance in puppies has yet to be evaluated in a more diverse population of companion dogs. In this study, companion dogs under 12 months of age were tested once on two tasks purported to measure aspects of executive function: the delayed-search task (DST) and the detour reversal task (DRT). Owners also filled out the Canine Behavioral Assessment and Research Questionnaire (C-BARQ) to evaluate how temperament influenced task performance. Contrary to prior research, performance did not improve with age on either task. However, the lack of age effects was likely the result of small sample sizes and individual differences across other factors influencing performance. Specifically, temperament differences as measured by the C-BARQ subscales for nonsocial fear and excitability predicted task performance on the DST, but the effect of temperament on task performance differed between males and females. Excitability also predicted performance on the DRT, but the effect depended on the age of the dog. In addition, no correlations were observed between task measures, indicating a lack of construct validity. Overall, these findings provide a preliminary analysis of factors that appear to influence cognitive task performance in young companion dogs and highlight suggestions for future research evaluating the impact of individual differences on cognitive performance.